Introduction to the Polian Approach to the Mental Limit: a Poposal (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
Knowledge is the most powerful human tool for opening up to reality. What is the scope of this tool? What is its most important limit? Leonardo Polo detects in the very functioning of human knowledge what he calls mental limit. Its main consequence is that it hinders our access to reality, supplanting real being by mental presence. Polo explains that recognizing this problem is the first step to solve it. This article proposes an accessible approach to the Polian method, explaining the context in which it arises and using, for that purpose, a didactic text by García Morente.
Keywords: Leonardo Polo; mental limit; knowledge; being; reality; object